Ensuring stability of radar field when creating hydrometeorological monitoring system - Perelygin, B.V. (Radiotekhnika, 2018)
Based on the model of the radar field formed by a group of meteorological radars, the radar field characteristics are calculated for different radar location variants based on a geometric approach. A failure of a part of the radar is simulated for each of the field construction variants and the degree of stability of the continuous radar field is quantitatively assessed upon the failure of a part of the radar. Recommendations are given on the construction of a systematically stable radar field.